Effects of primary school's physical environment on children's spatial perception and behavior: The case of Kagithane, Istanbul, Turkey. (15th July 2019) - Türel, Ahmet; Ayşe Gür, Elmira
Abstract : Purpose: The relationship between the child and his/her physical environment is an area of interaction that includes social, psychological and cultural factors along with the spatial experience, perception and behavior of the child. This study is based on the effects of spatial perception and behavior of the child within the physical environment of primary schools. In this direction, the purpose of this paper is to investigate how spatial and physical characteristics of primary school typologies affect the spatial perception and behavior of the child. Also, the parameters affecting spatial perception and behavior are examined. Design/methodology/approach: The question to be investigated is how the spatial and physical characteristics of the school's physical environment affect the child's spatial perception and behavior in primary schools with different typologies. Within this scope, Istanbul's Kagithane region is selected as a case study. Schools are chosen for their similar spatial and dimensional features and similar socio-economic environment. The methodology of the study consists of a literature review, an observational study carried out to discover the interaction between the child and his/her school building and the analysis of the student's cognitive maps. These maps were evaluated according to topological, projective, metric and imaginative parameters. Findings: The results show spatial organization and physical characteristics of primary school buildings with a structure that allows for change and transformation, and contributes to the physical and cognitive development of children. Originality/value: This study will provide an opportunity to develop the design of future primary school buildings that can support the spatial perception and spatial experiences of the children.